Debt-Based Hajj Financing Models: Legal Foundations and Socio-Economic Implications in DSN-MUI Fatwa - Abd Razak; Badrul Munir; Husni Mubarrak; Zulkhairi Zulkhairi; Anshar Zulhelmi; Suraiya Suraiya (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2025)
This article provides an analytical study of the legal reasoning and arguments underpinning the DSN-MUI fatwa that permits Hajj financing through debt and financing schemes. Utilizing a descriptive literature review, the study traces relevant fatwas and examines their sharia bases, particularly the principles of maqasid al-shari'ah such as al-ibāhah (permissibility) and manhaj al-taysir (the approach of ease). The research aims to explore how this fatwa adapts to modern economic contexts while preserving core sharia principles, particularly regarding the reinterpretation of istitha’ah (capability). Findings demonstrate that the fatwa is fundamentally supported by a paradigm oriented toward achieving maslahat (benefit) and dar’ al-mafsad (avoidance of harm), emphasizing justice and accessibility for Muslim communities seeking to perform Hajj via sharia-compliant financing. This study offers in-depth insights into the legal construction and foundational sharia principles used by DSN-MUI, contributing critical perspectives on the social and economic implications of debt-based Hajj financing for scholars, Islamic finance practitioners, and policymakers.